2019
DOI: 10.1002/aqc.3154
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive ecology of the threatened and endemic freshwater mussel Lampsilis bracteata

Abstract: The Texas fatmucket, Lampsilis bracteata, is a unionid mussel endemic to the Colorado and upper Guadalupe River basins of Central Texas and a candidate for federal listing under the Endangered Species Act. There is increased interest in propagation and population restoration of threatened mussels in Texas as a potential conservation method, but still little is known about their life histories and how local populations may differ in aspects of their reproductive ecology, e.g. timing of brooding and potential lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
1
8
1
Order By: Relevance
“…Researchers have shown that gametogenesis can occur year round in many tachytictic species (Holland-Bartels and Kammer 1989;Jirka and Neves 1992;Garner et al 1999;Tsakiris et al 2016), which was observed in C. petrina in the Llano River, but not in the San Saba River. Similar to findings from another study investigating Lampsilis bracteata in central Texas (Seagroves et al 2019), reproduction appeared to be more limited at sites in the San Saba River compared to the Llano River as suggested by a larger number of samples without gametes found in the San Saba River compared to the Llano River (43% vs. 11% when comparing months in which both rivers were sampled). Detrimental environmental conditions in the San Saba River may play a role, either by causing reproductive senescence in mussels as exhibited in populations of other taxa (Nussey et al 2013) or by making mussels more susceptible to diseases and parasites (see below).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Researchers have shown that gametogenesis can occur year round in many tachytictic species (Holland-Bartels and Kammer 1989;Jirka and Neves 1992;Garner et al 1999;Tsakiris et al 2016), which was observed in C. petrina in the Llano River, but not in the San Saba River. Similar to findings from another study investigating Lampsilis bracteata in central Texas (Seagroves et al 2019), reproduction appeared to be more limited at sites in the San Saba River compared to the Llano River as suggested by a larger number of samples without gametes found in the San Saba River compared to the Llano River (43% vs. 11% when comparing months in which both rivers were sampled). Detrimental environmental conditions in the San Saba River may play a role, either by causing reproductive senescence in mussels as exhibited in populations of other taxa (Nussey et al 2013) or by making mussels more susceptible to diseases and parasites (see below).…”
Section: Discussionsupporting
confidence: 81%
“…Parasitic infection rates in mussels are usually low (,6%; Haag and Stanton 2003), but some studies have shown relatively high (20-36%) infection rates in multiple species (Zale and Neves 1982;Tsakiris et al 2016;Dudding et al 2020). In the San Saba River, during congruent sampling trips, bucephalid trematodes (Bucephalidae) and unidentified parasites were found in gamete samples of Lampsilis bracteata (6% infection rate for all individuals) consistently and in low abundance from February 2017 to February 2018 but were not found in April and September 2017 (Seagroves et al 2019). Conversely, parasites in our study were found mostly during the summer and fall months (June-November) in both Cyclonaias species.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations